Evidence for a chromosome origin unwinding system broadly conserved in bacteria. Issue 13 (1st July 2021) - Pelliciari, Simone; Dong, Mei-Jing; Gao, Feng; Murray, Heath
Abstract: Genome replication is a fundamental requirement for the proliferation of all cells. Throughout the domains of life, conserved DNA replication initiation proteins assemble at specific chromosomal loci termed replication origins and direct loading of replicative helicases (1 ). Despite decades of study on bacterial replication, the diversity of bacterial chromosome origin architecture has confounded the search for molecular mechanisms directing the initiation process. Recently a basal system for opening a bacterial chromosome origin ( oriC ) was proposed (2 ). In the model organism Bacillus subtilis, a pair of double-stranded DNA (dsDNA) binding sites (DnaA‐boxes) guide the replication initiator DnaA onto adjacent single-stranded DNA (ssDNA) binding motifs (DnaA‐trios) where the protein assembles into an oligomer that stretches DNA to promote origin unwinding. We report here that these core elements are predicted to be present in the majority of bacterial chromosome origins. Moreover, we find that the principle activities of the origin unwinding system are conserved in vitro and in vivo . The results suggest that this basal mechanism for oriC unwinding is broadly functionally conserved and therefore may represent an ancestral system to open bacterial chromosome origins.